Genome‐wide association study identifying novel variant for fasting insulin and allelic heterogeneity in known glycemic loci in Chilean adolescents: The Santiago Longitudinal Study. Issue 7 (30th December 2020) - Buchanan, Victoria L; Wang, Yujie; Blanco, Estela; Graff, Mariaelisa; Albala, Cecilia; Burrows, Raquel; Santos, José L; Angel, Bárbara; Lozoff, Betsy; Voruganti, Venkata Saroja; Guo, Xiuqing; Taylor, Kent D; et al.
Summary: Background: The genetic underpinnings of glycemic traits have been understudied in adolescent and Hispanic/Latino (H/L) populations in comparison to adults and populations of European ancestry. Objective: To identify genetic factors underlying glycemic traits in an adolescent H/L population. Methods: We conducted a genome‐wide association study (GWAS) of fasting glucose (FG) and fasting insulin (FI) in H/L adolescents from the Santiago Longitudinal Study. Results: We identified one novel variant positioned in the CSMD1 gene on chromosome 8 (rs77465890, effect allele frequency = 0.10) that was associated with FI ( β  = −0.299, SE = 0.054, p  = 2.72×10 −8 ) and was only slightly attenuated after adjusting for body mass index z‐scores ( β  = −0.252, SE = 0.047, p  = 1.03×10 −7 ). We demonstrated directionally consistent, but not statistically significant results in African and Hispanic adults of the Population Architecture Using Genomics and Epidemiology Consortium. We also identified secondary signals for two FG loci after conditioning on known variants, which demonstrate allelic heterogeneity in well‐known glucose loci. Conclusion: Our results exemplify the importance of including populations with diverse ancestral origin and adolescent participants in GWAS of glycemic traits to uncover novel risk loci and expand our understanding of disease aetiology.